Macrodactyly: report of eight cases of a rare anomaly - Kostakoğlu, Naci; Kayıkçıoğlu, Aycan; Şafak, Tunç; Özcan, Gürhan; Keçik, Abdullah; Gürsu, Güler (The Turkish Journal of Pediatrics, 1996)
Macrodactyly or megalodactyly is a rare anomaly of the extremities. Neural factors are involved in the etiology. Presented here are eight cases which comprise five macrodactylous toes and three fingers. The mean age at first referral was 6.8 years. Six patients underwent resection of the proximal phalanges together with bulk reduction of the soft tissue mass. Only soft tissue reduction was performed in the remaining two patients. Skin necrosis was observed in two cases, one of which necessitated amputation at the proximal interphalangeal joint level. The functional outcome was evaluated as poor with limited range of motion and stiffness in the joints. As far as functional results are concerned, macrodactylous toes had a better prognosis than that of fingers.It was concluded that none of the available methods as yet gives ideal functional and cosmetic results in macrodactyly.
Keywords: macrodactyly; megalodactyly